2019
DOI: 10.1186/s13000-019-0825-1
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic small round cell tumor of the parotid gland-report of a rare case and a review of the literature

Abstract: Background Desmoplastic small round cell tumor (DSRCT) is a rare soft tissue tumor that generally involves the retroperitoneum, pelvis, omentum and mesentery in younger patients. However, extra-abdominal DSRCT is very rare. Case presentation A 49-year-old Japanese man noticed a mass in the right parotid gland. Ultrasound examination revealed a solid tumor about 2 cm in diameter. Computed tomography (CT) of the whole body revealed no other tumors or lymph node swelling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…DSRCTs are less frequently reported in other locations such as the pleura (31), lung (49), parotid gland (26), kidney (12), pancreas (43), paratesticular region (3,44) or bone and soft tissues of the extremities (1,3,55). Seven intracranial DSRCT cases with confirmation of EWSR1-WT1 fusion have been reported previously (3,9,40,50,52).…”
Section: Introductionmentioning
confidence: 99%
“…DSRCTs are less frequently reported in other locations such as the pleura (31), lung (49), parotid gland (26), kidney (12), pancreas (43), paratesticular region (3,44) or bone and soft tissues of the extremities (1,3,55). Seven intracranial DSRCT cases with confirmation of EWSR1-WT1 fusion have been reported previously (3,9,40,50,52).…”
Section: Introductionmentioning
confidence: 99%
“…Other diagnoses like malignant melanoma, Merkel cell carcinoma, metastatic neuroblastoma, Ewing sarcoma, rhabdomyosarcoma or malignant lymphoma are more common. Also, we should differentiate it from a solid variant of an adenoid cystic carcinoma [2].…”
Section: Discussionmentioning
confidence: 99%
“…DSRCT cases in major salivary glands have been reported but in a very small number of patients. The origin of this tumor is not well-known, and some authors hypothesize that it could derive from mesothelial or submesothelial cells because of the usual location and because of the positivity for antigens like desmin and Wilms tumor 1 (WT-1) [2]. In this report, we present a case of a DSRCT involving the parotid gland of a young male.…”
Section: Introductionmentioning
confidence: 87%
“…One recent retrospective analysis reported on 16 such cases, occurring in the head/neck, intracranial, thigh, axilla, paratesticular, intraosseous, and uterine corpus, and a single case of a pediatric ocular primary DSRCT has also been reported . A recent review of the literature describing major salivary gland DSRCT found only six published cases, with five of those occurring in adult patients (range of 23‐49 years old at presentation) . The only pediatric case previously described was in a five‐year‐old male with a parotid lesion; no clinical data with regard to cancer‐directed therapy or outcome are available .…”
mentioning
confidence: 99%
“…7 A recent review of the literature describing major salivary gland DSRCT found only six published cases, with five of those occurring in adult patients (range of 23-49 years old at presentation). 8 The only pediatric case previously described was in a five-year-old male with a parotid lesion; no clinical data with regard to cancer-directed therapy or outcome are available. 9 Of the five adult patients with outcome data in this series, three were alive and free of disease at the time of their reports, ranging from 7 to 36 months after the completion of therapy.…”
mentioning
confidence: 99%